Autoethnographie du Printemps érable: Revisiting Strike Narratives 10 Years Later - Dahl, Audrey; Jackson, Renée (The Canadian Journal for the Study of Adult Education / La revue canadienne pour l’étude de l’éducation des adultes)

(untitled) (Canadian Association for the Study of Adult Education / L’Association canadienne pour l’étude de l’éducation des adultes, 2024)
Over a decade ago, Québec witnessed the Printemps érable, a general student strike that emerged in early 2012 and transformed into a social movement with broad mobilization throughout the summer. This paper is based on two narratives written by the authors about our experience in what is known today as the biggest student strike in Canada. Using autoethnography, we return to our 2012 writings (“I am Going to Meet Audrey” and “L’accident démocratique”) to reflect on our past and present learning. We ask ourselves: what comes to mind, looking back at these texts 10 years later? We discuss the interconnection between the personal and the political and how friendship developed our understanding of learning about solidarity. Overall, this autoethnographic practice brought us to significant realizations through critical engagement with our past perceptions.